Gambaran Resiliensi pada Anak yang Memiliki Keluarga Tiri - Melyana, Khairani (Happiness: Journal of Psychology and Islamic Science, 2022)
Every child has a desire to have a harmonious family. In reality, not every family can make it happen, because every family has various problems. Problems that occur in the family include divorce, death of a partner and others. Various problems that occur in the family will have an impact on family members, one of which is the child. The purpose of this research is to know the description of resilience in children who have step families. The type of research used in this research is qualitative research with phenomenological methods. Data collection was carried out using interview techniques, using interview guides (guide interviews) and coding the results of the interviews. Subjects were taken based on certain criteria using a purposive sampling technique. Respondents from this study were children who have step families. The results of this study found several categories, namely the relationship with the stepfamily, emotional control, self-acceptance and also the ability to overcome problems within oneself and the family.